TEACHING VOCABULARY USING ANIMAL PICTURES AS A TEACHING AID: THE CASE OF THE FOURTH GRADE STUDENTS OF SD (ELEMENTARY SCHOOL) 2 PAPRINGAN, KUDUS - Ulin Nafiati (Universitas PGRI Semarang, 2013)
The objectives of the study are (1) To find out the vocabulary mastery of the fourth grade students of SD 2 Papringan using animal pictures, (2) To know the problem faced by the fourth grade students of SD 2 Papringan in studying vocabulary using animal pictures, and (3) To know the possible solutions to overcome the problems are faced by the fourth grade students of SD 2 Papringan in studying vocabulary using animal picture. The subjects are all the fourth grade students of SD 2 Papringan. The total number of the students are 28 students. This research used the descriptive qualitative method. The research instruments used test and questionaire. The result of the result shows that (1) Students’ vocabulary using animal pictures as a teaching aid is appropiate in teaching vocabulary. It is proven of the test result that 11 (39%) students who got A (Outstanding), 9 (23%) students who got B (Above average), 8 (29%) students who got C (Average), 0 (0%) student who got D (Below average), and 0 (0%) student who got E (Insufficient). It indicates that most of the students are able to do the test because the mean of the students’ score is 81, 57. (2) In teaching learning process there were some problems faced by students are; the students of the fourth grade do not like learning English, they do not know about simple English vocabulary, the students of the fourth grade do not know the English animal names, the students of the fourth grade feel difficult in learning vocabulary without using picture, and the students of the fourth grade do not like to be taught vocabulary, especially animal without pictures. (3) For possible solutions to overcome the problems faced by the students are; the teacher has to select the interesting media to the students in learning English in order to make the students feel enjoy in studying, the teacher should give more information about English animal names, the teacher has to use picture as the teaching aid in order to avoid difficulties in teaching and learning vocabulary, and the teacher has to use picture as a teaching aid to attract the students’ interest in learning vocabulary in particular about animal pictures, so they do not feel bored.